1993
DOI: 10.1001/archpsyc.1993.01820150045004
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoautosomal Locus for Schizophrenia Excluded in 12 Pedigrees

Abstract: A pseudoautosomal locus for schizophrenia has been proposed based on observations of an excess of same-sex affected sibling pairs over opposite-sex pairs when the transmitting parent is the father. Such a pattern of partial concordance by sex related to paternal transmission would be difficult to explain by any biologic mechanism other than pseudoautosomal transmission of schizophrenia. To test the pseudoautosomal hypothesis, 37 sibling pairs concordant for the schizophrenia spectrum were identified from 24 nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…A pseudoautosomal locus for a schizophrenia susceptibility gene that would account for these differences was suggested [Crow et al, 1989]. An early study using sib pair analysis reported evidence of excess sharing at DXYS14 [Collinge et al, 1991], that was supported in one nonparametric replication , but was not supported by a number of other studies using both parametric and nonparametric analyses Wang et al, 1993;Crow et al, 1994;Barr et al, 1994;Maier et al, 1995;Kalsi et al, 1995c]. A large collaborative study examining markers within band Xp11 near the MAO loci found a LOD of 1.97 under a dominant model for DXS7 in a set of 92 sib pairs selected for maternal inheritance.…”
Section: Chromosomementioning
confidence: 99%
“…A pseudoautosomal locus for a schizophrenia susceptibility gene that would account for these differences was suggested [Crow et al, 1989]. An early study using sib pair analysis reported evidence of excess sharing at DXYS14 [Collinge et al, 1991], that was supported in one nonparametric replication , but was not supported by a number of other studies using both parametric and nonparametric analyses Wang et al, 1993;Crow et al, 1994;Barr et al, 1994;Maier et al, 1995;Kalsi et al, 1995c]. A large collaborative study examining markers within band Xp11 near the MAO loci found a LOD of 1.97 under a dominant model for DXS7 in a set of 92 sib pairs selected for maternal inheritance.…”
Section: Chromosomementioning
confidence: 99%
“…The link between schizophrenic loci and the pseudoautosomal X-Y chromosome locus has not been confirmed because of difficulties in replicating the previous published data ( Asherson et al, 1992;Wang et al, 1993;Barr et al, 1993;Curtis et al, 1993;Ishida et al, 1993;Wildenauer et al, 1993) and methodological uncertainties (Curtis and Gurling, 1990). Even so, it is important to emphasize that, in the work cited above, Collinge et al (1991) tested Crow's hypothesis using marker DNA for the telomeric pseudoautosomal locus, DXYS14, and concluded that, as expected, schizophrenic sibling pairs shared alleles on the DXYS14 locus, supporting the existence of a genetic link between DXYS14 and schizophrenia -result confirmed by D' Amato et al (1992Amato et al ( , 1994.…”
Section: Reviewmentioning
confidence: 92%
“…The pseudo-autosomal hypothesis predicts that when fathers transmit the disorder, schizophrenia-concordant sibling pairs are more likely to be concordant by gender than when mothers transmit the illness. Some studies have observed this pattern (Crow et al 1989;, whereas others have not (Asherson et al 1992;Maier et al 1993;Wang et al 1993). When molecular- (Asherson et al 1992;Wang et al 1993), but some have supported it (Collinge et al 1991;d'Amato et al 1992).…”
Section: Introductionmentioning
confidence: 96%
“…For decades there have been reports about a higher prevalence of same-gender sibling pairs than mixed-gender sibling pairs suffering from schizophrenia and related disorders (Mott 1910;Myerson 1925;Schulz 1932;yon Zehnder 1941;Penrose 1942;Rosenthal 1962;Tsuang 1967;Crow et al 1989;Crow 1991;Shimizu et al 1991;Asherson et al 1992;Gorwood et al 1992;Maier et al 1993;Wang et al 1993). Sturt and Shur (1985) and Curtis and Gurling (1990) argued that diagnostic heterogeneity, methodological errors in statistical analysis and incomplete biased sampling Harald N. Aschauer (5:~) 9 Kurt Meszaros 9 Ulrike Willinger Gabriele Fischer 9 Rainer Strobl 1 -Henriette Beran Elisabeth Lenzinger 9 Eleonore Reiter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation